Satellite instructional television experiment : UN-UNESCO Panel Meeting on SITE Experiences, October 31-November 5, 1977 (Space Applications Centre, Indian Space Research Organisation, Govt. of India, 1978)
Report of the third meeting on the impact of satellite-based instructional experiences, chiefly in the field of community development, on the people of rural India.